PENERAPAN PEMBELAJARAN DISCOVERY UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 1 MARONG TAHUN AJARAN 2016/2017 - Nistia Reni Andari; Lalu M. Tauhid; Ratnadi Ratnadi; Heri Hadi Saputra (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2020)
Based on the results of observations and interviews with teachers of class V of SDN 1 Marong obtained information that in IPA lessons the average score of student exams in the first semester of the 2015/2016 School Year, was 70. The average value is still below the Minimum Completion Criteria (KKM) that has been determined, which is 75. One of the problems faced by students is the lack of IPA learning with interesting and challenging. From these problems, researchers conduct research with the application of discovery learning. This research is carried out in 2 cycles, where each cycle consists of 4 stages, namely: planning, implementation, observation, and reflection. The indicator of research success, is if classically 85% of all students get a grade of  75. From the results of the analysis of the evaluation value of cycles I and II obtained by the data, the average value in cycle I was obtained 72.8 with a classical completeness of 73%. After reflection on the improvement plan in cycle II in the form of; heterogeneous group division and guidance evenly in each discussion group and in each student, the average score obtained by 80 with the classical completion of students in cycle II by 88%, an increase of 15% from cycle I. From the results of this study it can be concluded that by applying discovery learning that is carried out optimally can improve the learning outcomes of students in class V of SDN 1 Marong School Year 2016/2017